Vasogenic brain edema during maintenance hemodialysis - Schaier, Matthias; Wolf, Robert Christian; Kubera, Katharina Maria; Nagel, Simon; Bartsch, Andreas J.; Zeier, Martin; Bendszus, Martin; Herweh, Christian (Clinical neuroradiology, 2021)
Hemodialysis (HD), especially when first initiated, can cause neurological deterioration. Presumably this is due to transient cerebral edema, which has been observed using diffusion weighted magnetic resonance imaging (MRI) in experimental and human studies; however, this has not been investigated under maintenance hemodialysis (mHD). Moreover, there are no studies to date investigating regional effects of mHD on grey and white matter volumes.
Published online: 17 December 2019
Gesehen am 16.07.2021